Wayang Puppets and Listening to Folk tales: Efforts to Improve Elementary Student’s Literacy - Fatikha, Rosita Febriani; Marmoah, Sri; Azman, Mohamed Nor Azhari (Universitas Sebelas Maret, 2025)
The background for this study is rooted in the observed challenges in developing robust literacy skills in young learners, coupled with the rich cultural heritage of Indonesia that offers unique and engaging learning opportunities. This literature study investigates the potential of integrating traditional Indonesian wayang performances and the act of listening to folk tales as pedagogical tools to enhance literacy among elementary school students. The primary objective was to explore how these traditional art forms can be systematically incorporated into the elementary school curriculum to foster reading comprehension, vocabulary acquisition, and critical thinking. As a literature review, the research method involved a comprehensive synthesis of existing scholarly articles, educational reports, and cultural studies pertaining to traditional storytelling, drama, and their impact on cognitive development and literacy. The findings suggest that both wayang and folk tales provide immersive narrative experiences that stimulate imagination, improve listening skills, and introduce a wide range of vocabulary and cultural concepts relevant to the curriculum. Furthermore, engaging with these art forms can cultivate a positive attitude towards reading and learning. In conclusion, the study advocates for the strategic integration of wayang and folk tales into elementary education as an effective and culturally sensitive approach to significantly improve students' literacy levels.